Comparing high‐dose cisplatin with cisplatin‐based combination chemotherapy in definitive concurrent chemoradiation setting for locally advanced head and neck squamous cell carcinoma (LAHNSCC). (9th April 2019) - Furqan, Muhammad; Snyders, Travis P.; Saqlain, Mohammed U.; Mott, Sarah L.; Laux, Douglas; Snow, Anthony; Anderson, Carryn M.; Watkins, John M.; Clamon, Gerald H.
Abstract: Background: High‐dose cisplatin (Cis) is a preferred systemic agent for concurrent chemoradiation (CRT) in locally advanced head and neck squamous cell cancer (LAHNSCC) patients. As some patients are unable to tolerate Cis, this study compares the toxicity and efficacy of weekly cisplatin‐paclitaxel (CP) regimen with Cis. Methods: Patients with LAHNSCC receiving definitive chemoradiation either with Cis (Cisplatin—100 mg/m 2 q3w x 3) or CP (Cisplatin—20 mg/m 2 ; Paclitaxel—30 mg/m 2 qw x7) were included. Results: Cis and CP groups were comprised of 114 and 111 subjects, respectively. Complete response for Cis versus CP groups was 88% versus 88%, respectively. Median follow‐up for the study was 58.5 months. After adjusting for potential treatment selection bias, no significant differences were evident between Cis and CP groups for overall survival (hazard ratios [HR] 0.85, 95% CI 0.59‐1.21, P = 0.36), progression free survival (HR 0.88, 95% CI 0.62‐1.24, P = 0.46), locoregional control (HR 0.77, 95% CI 0.52‐1.15, P = 0.21), and distant control (HR 0.87, 95% CI 0.61‐1.23, P = 0.42). Patients in the CP group had less acute and chronic toxicities. Conclusions: Weekly CP regimen can serve as an alternative systemic therapy with radiation in patients with LAHNSCC who are not fit for Cis. Abstract : Concurrent chemoradiation with weekly cisplatin and paclitaxel is tolerable and provide higher compliance rate in patients with locally advanced head and neck squamous cell carcinoma. Outcomes of patients on combination chemotherapy were similar to high‐dose cisplatin.